Water productivity in the Syr-Darya River Basin - Murray-Rust, Hammond; Abdullaev, Iskandar; Ul-Hassan, Mehmood; Horinkova, Vilma M. (International Water Management Institute, 2003)
This report analyses water productivity and water-saving initiatives in the Syr-Darya river basin in Central Asia and presents institutional and political aspects of water management in the basin.